2022
DOI: 10.1038/s41419-022-05081-4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond controlling cell size: functional analyses of S6K in tumorigenesis

Abstract: As a substrate and major effector of the mammalian target of rapamycin complex 1 (mTORC1), the biological functions of ribosomal protein S6 kinase (S6K) have been canonically assigned for cell size control by facilitating mRNA transcription, splicing, and protein synthesis. However, accumulating evidence implies that diverse stimuli and upstream regulators modulate S6K kinase activity, leading to the activation of a plethora of downstream substrates for distinct pathobiological functions. Beyond controlling ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 243 publications
(304 reference statements)
0
20
0
Order By: Relevance
“…RSK2, as the downstream signaling mediator of the RAS/ERK pathway, has been shown to play critical roles in oncogenesis and tumor progression in various cancerous diseases, using its NTKD as an output hub to activate its series of oncogenic substrates 41–44 . The involvement of S6K in lymphomagenesis has rarely been reported; however, S6K is also known to be involved in tumorigenesis in various cancers 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSK2, as the downstream signaling mediator of the RAS/ERK pathway, has been shown to play critical roles in oncogenesis and tumor progression in various cancerous diseases, using its NTKD as an output hub to activate its series of oncogenic substrates 41–44 . The involvement of S6K in lymphomagenesis has rarely been reported; however, S6K is also known to be involved in tumorigenesis in various cancers 45 …”
Section: Discussionmentioning
confidence: 99%
“…involvement of S6K in lymphomagenesis has rarely been reported; however, S6K is also known to be involved in tumorigenesis in various cancers. 45 Based on these findings, we examined and successfully demonstrated the antilymphoma efficacy of the RSK/AKT/S6K triple inhibitor TAS0612 by modulating cell cycle regulation and inducing apoptosis in BCL-derived cell lines. Although we did not perform an in vivo mice model study due to the lack of a reliable disease model with our cell lines, we showed the ex vivo efficacy of TA0612 in patient-derived B-lineage lymphoma cells of various disease subtypes, and the clinical activity and safety of TAS0612 are currently under evaluation in a clinical trial involving patients with locally advanced or metastatic solid tumors.…”
Section: F I G U R Ementioning
confidence: 99%
“…*p < .05, **p < .01. the phosphorylation of insulin receptor substrate 1 (IRS1) S1101 and desensitization of the insulin receptor. 22,43 S6K1-deficient mice are resistant to HFD-induced hyperglycemia and obesity. 44 We recently reported that gingerenone A, a natural product of the ginger extract, and astaxanthin, a natural, pigmented xanthophyll carotenoid commonly present in microalgae, yeasts, salmon, trout, krill, and other seafood, inhibit S6K1 activity, sensitize the insulin receptor, and increase glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…21 Ribosomal protein S6 kinase 1 (S6K1), a serine/threonine kinase downstream of mTOR, phosphorylates the insulin receptor substrate (IRS) at S1101 site and subsequently attenuates the activation of the PI3K pathway. 22 S6K1 is constitutively activated under the nutritional overload condition, leading to insulin resistance and inducing obesity. 23 S6K1 is also involved in regulating the expression of a variety of energy expenditure-related genes such as melanocortin-4 receptor (MC4R).…”
Section: Introductionmentioning
confidence: 99%
“…So, Nrf2 has basic roles for cardiac protection through activating by GCs-beta synthesis which promote mineralocorticoid synthesis for protecting hart layers from K and Na binding toxicity. And, NRF2 drives the cell cycle entry and differentiation, that appears to be beneficial for recovery from blood loss (through activating both Ang2-AT2 and VEGF-A synthesis) [118].…”
Section: Nrf2 Is Necessary For Adopting Anti-inflammatory Growth and ...mentioning
confidence: 99%